Role of NEP 2020 Policy in the Higher Education System - Yadav, Aditya Singh; Saxena, Tulika; Kumar, Prashant; Dixit, Akhilesh Kr.; Anuradha; Yadav, Nidhi (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The National Education Policy (NEP) 2020 aims to reshape higher education in India by introducing a broad framework that encourages innovation, creativity, flexibility, and learning across different subjects. It seeks to reform the current system by promoting a more well-rounded approach to education, encouraging students to think critically, and offering opportunities for lifelong learning. NEP 2020 emphasizes creating large, multidisciplinary institutions, offering flexible programs, and encouraging research and development at all levels. It also restructures undergraduate and graduate programs to provide multiple entry and exit points, allowing students to customize their education based on their individual needs. Additionally, NEP 2020 focuses on making Indian universities more globally connected and aims to increase the gross enrolment ratio to 50%.